Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $r, s$ be integers and let $$a = (2011)^2 + (2011)r + s$$ and $$b = (2012)^2 + (2012)r + s$$ Show that there exists an integer $c$ with $c^2 + rc + s = ab$.

Can anyone help me with this?

share|improve this question
    
My answer concluded that the 2011 and 2012 does not matter and it could be anything as long as they are t and t+1. Is the consensus that that is true? –  kaine Sep 12 '13 at 20:16

4 Answers 4

up vote 1 down vote accepted

Subtracting the first equation from the second, we have
$r = b-a-2012^2+2011^2 = b-a - (2012+2011) = (b-2012) + (-a-2011)$

Multiplying the first equation by $2012$, the second by $2011$ and subtracting, we have
$s = 2012a - 2011b - 2012\cdot 2011^2 + 2011\cdot 2012^2 = 2012a - 2011b + 2011\cdot 2012$

So $s - ab = -ab + 2012a - 2011b + 2011\cdot 2012 = (b-2012)\cdot(-a-2011)$

Thus we have clear choices for the sum and product of the roots of $c^2 + rx + s = ab$.

share|improve this answer

$$a=t^2+rt+s$$ $$b=(t+1)^2+r(t+1)+s=t^2+2t+1+rt+r+s$$ $$ab = c^2+cr+s=(t^2+rt+s)(t^2+2t+1+rt+r+s) = a(a+2t+1+r)$$ $$c = 1/2(\sqrt{r^2-4s+4ab}-r)$$ c is an integer iff $r^2-4s+4ab$ is a perfect square and $\sqrt{r^2-4s+4ab}-r$ is even $$r^2-4s+4ab = r^2+4a^2+8at+4a+4ar-4s$$ substiting back in a yields $$r^2-4s+4ab = (2rt+r+2s+2t^2+2t)^2$$

note that the $\sqrt{r^2-4s+4ab}-r = 2(rt+s+t^2+t)$

share|improve this answer
    
Could you tell me a bit more about how you simplified the fifth equation after substituting a? –  Yadnarav3 Sep 13 '13 at 3:18
    
I assumed that r,2s,and $2t^2$ would be parts of the number that would appear under the exponent in equation 5 due to the presence of r^2, 4s^2, and 4t^4. I then expanded $(r+2s+2t^2+2k)^2$ to solve for k, got bored, and finished it on wolfram alpha. –  kaine Sep 13 '13 at 15:19

The quadratic equation $c^2+rc+s-ab=0$ has two solutions, namely $$ c=(2011r+s+2011\cdot 2012), $$ or $$ c=-(2012r + s + 2011\cdot 2012) $$ And indeed, with this choice of $c$ it works.

share|improve this answer

Choose r = 2 and s = 1

Then 2011^2 + 2.2011 + 1 = a and 2012^2 + 2.2012 + 1 = b

a = (2011 + 1)^2 b = (2012 + 1)^2

ab = (2012.2013)^2 Let 2012 = u

ab = (u(u+1))^2 ab = u^4 + 2u^3 + u^2

Let c = au^2+bu+l

ab = (au^2+bu+l)^2 + (au^2 + bu +1)*2 + 1

Expanding the expression

a^2 = 1 > a = 1 2ab = 2 > b = 1 b^2 + 2ac + 2a = 1 > c = -1

Thus c = (u^2 + u -1) which is an integer as u is an integer

Goes to prove that ab = c^2 + c*2 + 1 holds true for an integer c.

Thanks

Satish

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.